RELATIVELY IMPAIRED CORTISOL SUPPRESSION BY DEXAMETHASONE IS ASSOCIATED WITH LEFT VENTRICULAR MASS AND GEOMETRIC CHANGES IN PATIENTS WITH ESSENTIAL HYPERTENSION. (June 2018) - Catena, C.; Colussi, G.; Marileda, N.; Abrusci, R.; Frangipane, A.; Duratti, A.; Sechi, L.A.
Abstract : Objective: Both subclinical hypercortisolism and overt Cushing syndrome are associated with cardiovascular events and changes in left ventricular (LV) geometry. However, few data are available on the relationship between cortisol production and LV mass and geometry in essential hypertensive (EH) patients. Design and method: In 103 EH subjects (age 50 ± 14 y, 58 males, 33 never treated with antihypertensive drugs), we evaluated clinical characteristics, renal function, plasma levels of glucose, insulin, and lipids, the circadian levels of plasma cortisol (8 AM, 5 PM, and 11 PM) with the area under the curve (C-AUC), 24-h urinary cortisol excretion, and the response of plasma cortisol to an overnight suppression test with 1 mg of dexamethasone (DMT). Echocardiography was performed in all patients with a standard technique. Results: LV hypertrophy (LVH) according to current criteria was detected in 34 of 103 EH patients. Patients with LVH were significantly older, had longer duration of hypertension, and greater BMI, systolic blood pressure, plasma triglycerides, and post-DMT plasma cortisol level (P = 0.004) than patients without LVH. No differences were detected in circadian plasma cortisol profile nor urinary cortisol excretion between with and without LVH. Eccentric LVH was present in 13 EH patients who showed greater post-DMT plasma cortisol levels than patients with other types of LV geometry. In a logistic regression model, LVH was associated independently with BMI (OR 1.20, P = 0.022) and post-DMT plasma cortisol (OR = 1.06, P = 0.045). LV mass index (LVMI) was significantly and directly related to age (r = 0.329, P = 0.001), duration of hypertension (r = 0.243, P = 0.015), BMI (r = 0.317, P = 0.001), systolic blood pressure (r = 0.397, P < 0.001), plasma glucose (r = 0.215, P = 0.031) and triglycerides (r = 0.323, P = 0.001), HOMA-index (r = 0.226, P = 0.029), and post-DST plasma cortisol (r = 0.349, P = 0.002), whereas a borderline significant relationship was found with C-AUC (r = 0.201, P = 0.053). In multivariate regression models, LVMI was independently associated post-DMT cortisol (B = 0.245, P = 0.026) and C-AUC (B = 0.233, P = 0.018). Conclusions: Subtle changes in the regulation of plasma cortisol secretion contribute to cardiac hypertrophy and LV geometric changes in patients with EH.